Tantangan dan Efektivitas Peran Wakil Kepala Daerah dalam Implementasi Kebijakan Pemerintah Daerah (Studi Kasus DKI Jakarta) - Utama, Dedy Kusna (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2025)
Challenges and Effectiveness of Deputy Regional Heads’ Role in Local Government Policy Implementation (Case Study of Jakarta Capital Region) This study examines the role of deputy regional heads in Jakarta Capital Region (DKI Jakarta) and the challenges they face in implementing local government policies. The research identifies key issues, including ambiguous authority delegation, political interference, and administrative inefficiencies. Using a qualitative approach, the study analyzes legislative documents, government data, and expert interviews to evaluate policy effectiveness. Findings reveal that power imbalances and bureaucratic obstacles hinder the deputy governor’s role, affecting governance stability and policy execution. Recommendations include establishing a clearer policy framework, codifying deputy heads’ responsibilities, reducing political intervention, enhancing coordination mechanisms, and ensuring leadership continuity. These measures aim to improve governmental efficiency and public service delivery in Jakarta and other local administrations. Abstrak Studi ini mengkaji peran wakil kepala daerah di DKI Jakarta dan tantangan yang mereka hadapi dalam pelaksanaan kebijakan pemerintah daerah. Penelitian ini mengidentifikasi isu-isu utama, termasuk ketidakjelasan delegasi kewenangan, pengaruh politik, dan ketidakefisienan administrasi. Menggunakan pendekatan kualitatif, penelitian ini menganalisis dokumen legislatif, data pemerintahan, dan wawancara dengan para ahli untuk mengevaluasi efektivitas kebijakan. Temuan menunjukkan bahwa ketidakseimbangan kekuasaan dan hambatan birokrasi menghalangi peran wakil gubernur, mempengaruhi stabilitas pemerintahan dan pelaksanaan kebijakan. Rekomendasi termasuk pembentukan kerangka kebijakan yang lebih jelas, pengusulan kebijakan yang dengan tegas menetapkan tugas wakil kepala daerah, pengurangan campur tangan politik, peningkatan mekanisme koordinasi, dan memastikan kelangsungan kepemimpinan. Langkah-langkah ini bertujuan untuk meningkatkan efisiensi pemerintahan dan penyampaian layanan publik di Jakarta dan pemerintah daerah lainnya.